Organic farming in Greece trends and perspectives - Bitsaki A.; Vassiliou A.; Kabourakis E. (The market for organic products in the Mediterranean region, 2003)
This paper constitutes a critical evaluation of the current status of organic agriculture in Greece, and aims to identify key factors influencing the development of organic farming in the country. Organic agricultural production and the national market for organic produce are constantly increasing. In this dynamic situation, data concerning the organic agriculture five years ago have little predictive value, in the same way that a description of the current situation will be of limited value in the future. Among the parameters examined were the following: National legislation, the Inspection and Certification Bodies operating in the country, those authorities competent for their accreditation, the number, area and regional distribution of organic farms, the main organic products, the number, type and location of processing units, the development of the national market for organic produce focusing on supply and demand, distribution channels and marketing strategies, common agronomic problems, research and training activities, and national policies governing organic agriculture.
Intensive Course in: Marketing of Organic Products, 2002/05/20-31, Izmir (Turkey)